A case of gastric antral vascular ectasia in which PuraStat, a novel self‐assembling peptide hemostatic hydrogel, was effective. Issue 1 (10th November 2022) - Misumi, Yoshitsugu; Takeuchi, Miharu; Kishino, Maiko; Kudo, Yoshimichi; Nonaka, Kouichi
Abstract: Gastric antral vascular ectasia (GAVE) is a gastric hemorrhagic disease associated with chronic liver disease. Argon plasma coagulation is widely used to control gastrointestinal bleeding due to GAVE. Although argon plasma coagulation is a relatively safe endoscopic procedure, it is not suitable in some cases, such as in patients with pacemakers. We report a case of GAVE in which PuraStat, a novel self‐assembling peptide hemostatic hydrogel, was effective. The patient was a 55‐year‐old man who had undergone Fontan surgery for tricuspid regurgitation more than 20 years prior. He developed hepatic cirrhosis as a complication following Fontan surgery. During upper gastrointestinal endoscopy to examine the cause of the progression of anemia and black stool, bleeding from GAVE was observed; PuraStat was applied to stop the bleeding. Postoperatively, the black stool disappeared, and his hemoglobin levels improved. Upper gastrointestinal endoscopy was performed 13 days after the surgery; the density of the capillaries in the antrum was significantly decreased, and a clear trend toward disappearance was observed. Therefore, the application of PuraStat may be useful in the treatment of GAVE.